2014
DOI: 10.11646/zootaxa.3846.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Two new Aprostocetus species (Hymenoptera: Eulophidae: Tetrastichinae), fortuitous parasitoids of invasive eulophid gall inducers (Tetrastichinae) on Eucalyptus and Erythrina

Abstract: Two closely related new species of Aprostocetus Westwood (Hymenoptera: Eulophidae: Tetrastichinae) are described as fortuitous parasitoids of invasive gall inducers in two other genera of Tetrastichinae, Leptocybe

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 760 publications
(21 citation statements)
references
References 23 publications
(11 reference statements)
0
21
0
Order By: Relevance
“…Aprostocetus causalis , a parasitoid of L. invasa in China, was described as a new species in 2014 [32]. However, the longevity of both sexes of this parasitoid in the laboratory was lower than the longevity found in a previous study carried out in Thailand [27], probably due to the different rearing method.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Aprostocetus causalis , a parasitoid of L. invasa in China, was described as a new species in 2014 [32]. However, the longevity of both sexes of this parasitoid in the laboratory was lower than the longevity found in a previous study carried out in Thailand [27], probably due to the different rearing method.…”
Section: Discussionmentioning
confidence: 99%
“…We presumed that this could be attributed to the population dynamics of Q. mendeli in Sichuan province, but this needs to be confirmed. Previous studies showed that Q. mendeli is a solitary idiobiont ectoparasitoid [15] while A. causalis and M. viggianii are solitary koinobiont endoparasitoids [32]. The competitive dynamics and mechanisms of both the ectoparasitoid ( Q. mendeli ) and endoparasitoids ( A. causalis and/or M. viggianii ) in L. invasa need to be studied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The highly invasive gall former, L. invasa , is attacked by local parasitoid species in eight countries so far (Protasov et al, 2008; Doganlar et al, 2013; Udagedara and Karunaratne, 2014; Yang et al, 2014) and by several spider species in China (Zheng et al, 2014). Local parasitoids also attack the wood borer, P. semipunctata , in Morocco, California, and South Africa (Fraval and Haddan, 1988; Hanks et al, 1997; Prinsloo, 2004) while its eggs are subject to predation by ants in Portugal (Way et al, 1992).…”
Section: Natural Enemiesmentioning
confidence: 99%